SUSTAINABLE NICKEL RECOVERY FROM NICKEL SLAG WASTE USING DIETHYLAMINE DITHIOCARBAMATE: ENHANCING RESOURCE EFFICIENCY AND MINIMIZING ENVIRONMENTAL IMPACT - Fadliah Fadliah; Muhammad Burhannudinnur; Paulina Taba; Abdul Wahid Wahab; Syahruddin Kasim; Abdul Karim; Hasri Hasri; Subandrio; Tri Widayati Putri; Arfiani Nur; Ghanima Yasmaniar; Ridha Husla; Sulistiani Jarre; Audrey Zahra; Eid Abdalrazaq; Shivaa Prasad Kollur; Indah Raya (Universitas Trisakti, 2025)
Slag waste from the metal refining industry, if left to accumulate for a long time, can become a source of environmental pollution due to the content of heavy metals that can dissolve and spread to the surrounding environment. However, slag can also be an alternative source for obtaining valuable metals. Aim: This study aims to examine the ability of diethylaminedithiocarbamate ligands to recover nickel metal from slag waste through the mechanism of complex compound formation. Methodology and results: The extraction process was carried out at the optimal pH for each ligand to maximize the selectivity and efficiency of metal recovery. Characterization of the complex compounds from the reaction was carried out using various analytical techniques, including Fourier Transform Infrared Spectroscopy (FTIR), UV-visible spectroscopy (UV-Vis), X-Ray Diffraction (XRD), Scanning Electron Microscopy with Energy Dispersive X-ray Spectroscopy (SEM-EDS), and melting point tests to determine the thermal stability of the compound. The study results indicate that diethylaminedithiocarbamate ligands can selectively form complex compounds with nickel metal in slag and are effective in recovering metals from slag waste with a recovery value of 94.88%. Conclusion, significance, and impact study: The results of this study indicate that using diethylaminedithiocarbamate ligands can be an environmentally friendly approach to using slag waste as a secondary source of metals.